1984
DOI: 10.1021/bi00319a015
|View full text |Cite
|
Sign up to set email alerts
|

Pupal and larval cuticle proteins of Drosophila melanogaster

Abstract: Proteins, soluble in 7 M urea, were extracted from third-instar larval and pupal cuticles of Drosophila melanogaster. Both extracts contain a limited number of polypeptides resolved by one- or two-dimensional electrophoresis. The five major larval proteins have low molecular weights (less than 20000) and are not glycosylated. The major pupal cuticle proteins fall into two size classes: two with apparent molecular weights of 56K and 82K and four with molecular weights between 15K and 25K. The proteins with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Low-molecular-weight proteins are also present in extracts from pupal and larval cuticles. In additions, these extracts contain high-molecular-weight and basic proteins [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…Low-molecular-weight proteins are also present in extracts from pupal and larval cuticles. In additions, these extracts contain high-molecular-weight and basic proteins [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the cells can incorporate radioactive oligosaccharide precursors into glycoproteins also in the presence of tunicamycin [2,6,7]. Analysis of the monosaccharide composition of glycoproteins synthesized by insect cells have in some cases demonstrated the presence of N-acetylgalactosamine [ 1,2,8]. Other investigators have shown that some glycoproteins isolated from insect cells can be probed with N-acetylgalactosamine specific lectins [ 1,2,9,10,1 I].…”
mentioning
confidence: 99%
“…Furthermore, the composition of both PCG-100 and PCP-82 oligosaccharides seems to be similar (Silvert et al, 1984;Boccaccio and Quesada, unpublished results).…”
Section: Discussionmentioning
confidence: 81%
“…Stage-specific, insoluble, insect larval and pupal cuticle proteins (PCP)* that can be extracted with 7 M urea or 1% SDS were previously found to be excellent differentiation markers (Chihara et al, 1982;Skelly and Howells, 1987;Roberts and Willis, 1980; Silvert et al, 1984). The synthesis of these proteins shows temporal regulation (Doctor et al, 1985;Boccaccio and Quesada-All&, 1989a;Kimbrell et al, 1988); this may be related to different cuticular location and/or function (for a recent discussion see Kimbrell et al, 1989).…”
Section: Introductionmentioning
confidence: 99%